Is There an Association between Type 1 Diabetes in Children and Gallbladder Stones Formation? - Al-Hussaini, Abdulrahman A. (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND AND AIMS: A number of studies in adults have evaluated the prevalence of gallstones in the diabetic population and showed a significant association with type 1 diabetes (T1D) and type 2 diabetes. The pediatric literature is limited to a single small case series. We conducted a cross-sectional study to evaluate for the presence of association between T1D in children and gallstones formation. PATIENTS AND METHODS: Children diagnosed with T1D in a diabetic clinic have been examined for existence of gall bladder stone formation from November 2008 through November 2009. All have been subjected to the following: History, physical examination, blood tests (liver function tests, lipid profile, glycosylated hemoglobin [HbA1C]), and an ultrasound (US) of the gall bladder. RESULTS: One hundred and five children with T1D have been enrolled consecutively over a 1-year period: age ranged between 8 months and 15.5 years, 62 patients were females. The mean age at diagnosis was 6.3 ± 2.9 years (range 0.85-11 years), mean duration of T1D was 2.2 ± 2.1 years (range 0.2-8 years), mean body mass index was 16.5 ± 3.4, mean HbA1c was 10.7 ± 2.4%, and 61.3% of patients had a HbA1c level >10%. The mean serum cholesterol was 4.16 ± 0.75 mmol/L (normal 3.65-5.15 mmol/L) and mean serum triglyceride 1.02 ± 1.3 mmol/L (normal 0-1.7 mmol/L). Two patients had hyperlipidemia. US of the gallbladder did not show any case of gallstones or sludge formation. CONCLUSION: Data from our study do not show any association between T1D in children and gallstones formation, with diabetes duration of less than 8 years. The relatively short duration of diabetes and possibility that our study was underpowered might have been reasons for the absence of any association.